Nonlinear H [infinity]-control, Hamiltonian systems and Hamilton-Jacobi equations - Aliyu, M. D. S. (Taylor & Francis, 2011)
A comprehensive overview of nonlinear H8 control theory for both continuous-time and discrete-time systems, Nonlinear H8-Control, Hamiltonian Systems and Hamilton-Jacobi Equations covers topics as diverse as singular nonlinear H8-control, nonlinear H8 -filtering, mixed H2/ H8-nonlinear control and filtering, nonlinear H8-almost-disturbance-decoupling, and algorithms for solving the ubiquitous Ham.